Consumption of Pistachio Nuts Beneficially Affected Blood Lipids and Total Antioxidant Activity in Rats Fed a High-Cholesterol Diet - (:unkn) unknown (CHARLES UNIV PRAGUE, FIRST FACULTY MEDICINE, 2009)
Although nuts are typically high in dietary fat, novel studies have shown that regular consumption of these heart-healthy foods might confer a beneficial effect on cardiovascular disease risk. In the present study, we aimed to analyse the effects of pistachio consumption on blood lipids, antioxidant activity, oxidative stress and siatic acid levels in high-fat-fed rats for 8 weeks. The oxidant-antioxidant status was evaluated by the determination of lipid peroxidation (thiobarbituric acid-reactive substances), total antioxidant activity, reduced glutathione content, activity of superoxide dismutase and total thiol levels. Furthermore, tissue damage was evaluated by total sialic acid levels in serum. Total cholesterol, triglycerides, sialic acid and thiobarbituric acid-reactive substances significantly increased whereas total antioxidant activity, reduced glutathione, total thiol levels significantly decreased in the hyperlipidaemic group compared to the control group. Pistachio consumption significantly decreased triglycerides and thiobarbituric acid-reactive substance levels and significantly increased total antioxidant activity in the hyperlipidaemic group. In conclusion, pistachio supplementation may improve blood lipids and ameliorate oxidative stress in experimental hyperlipidaemia, which may have beneficial applications in the prevention of cardiovascular diseases. However, its antioxidant mechanisms remain to be investigated.
Keywords: pistachio; antioxidants; oxidative stress; sialic acid; hyperlipidaemia; CORONARY-HEART-DISEASE; SIALIC-ACID; SERUM; GLUTATHIONE; ASSAY; PEANUTS; PLASMA; RISK; L.